Analisis Penerapan Kebijakan Protokol Kesehatan Pada Era New Normal Di Bandar Udara Notohadinegoro Jember - Dinar Sepbelawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
During the Covid-19 pandemic, all airports are required to comply with rules related to health protocols. The provision applies both to airport organizers, airline companies, passengers including officers or employees of airport organizers and airlines. This study aims to find out and analyze the Implementation of Health Protocol Policies in the New Normal Era at Notohadinegoro Jember Airport.This research uses qualitative research methods. Data sources are obtained through primary data and secondary data. Data collection methods use observation, interviews and documentation. Data analysis techniques are descriptively quantitative.The results showed that the implementation of new normal era health protocols on check-in area pasasi officers and supporting facilities and infrastructure in Bandar Udara Notohadinegoro Jember in accordance with the policy issued by the Minister of Transportation Number 13 of 2020 concerning Air Transportation Operations in the Community Activity Period Productive and Safe from Coronavirus Disease 2019 (COVID-19). However, there are still obstacles faced in implementing health protocol policies in the New Normal era on the protective equipment of check-in area pasasi officers, namely gloves that are easily wet so that they become optional protective equipment.